에너지 하베스팅 네트워크에서 최소 요구 보안 용량을 최대화하기 위한 시간 전환 기반의 아날로그 네트워크 코딩 - 이기송(Kisong Lee); 최현호(Hyun-Ho Choi) (한국정보통신학회논문지, 2017)
Recently, the energy shortage of sensors and the leakage of private information are considered as serious problems as the number of sensors is increasing due to the technological advance in Internet-of-Things. RF energy harvesting, in which sensors collect energy from external RF signals, and physical layer security become increasingly important to solve these problems. In this paper, we propose a time switching-based network analog coding for improving information security in wireless networks where the relay can harvest energy from source signals. We formulate 2-hop relay networks where an eavesdropper tries to overhear source signals, and find an optimal time switching ratio for maximizing the minimum required secrecy capacity using mathematical analysis. Through simulations under various environments, it is shown that the proposed scheme improves the minimum required secrecy capacity significantly, compared to the conventional scheme. 최근 사물 인터넷 기술의 발달로 인해 사용되는 센서의 수가 늘어남에 따라 센서의 전원 부족 및 사적인 정보의 유출이 심각한 문제로 여겨지고 있다. 이러한 문제들을 해결하기 위해 외부의 RF 신호로부터 전력을 수집하는 RF 에너지 하베스팅과 물리계층 보안 기술의 중요성이 점차 커지고 있다. 본 논문에서는 소스가 전송하는 신호로부터 에너지 하베스팅이 가능한 릴레이가 존재하는 무선 네트워크에서 정보 보안을 향상시키기 위한 시간 전환 기반 네트워크 아날로그 코딩 기법을 제안한다. 소스가 전송하는 신호를 도청하려는 도청자가 존재하는 2-hop 릴레이 네트워크를 모델링하고, 수학적 분석을 통해 최소 요구 보안 용량을 최대화 할 수 있는 최적의 시간 전환 비율을 찾았다. 다양한 환경에서 시뮬레이션을 통해 제안 방안이 기존 방안에 비해 최소 요구 보안 용량을 개선함을 보인다.